The Policies, Practices, and Politics of Women Representation in Political Parties: A Case Study of Women Members of Parliament in Regency/City-level Legislative Council Period 2014-2019 - Pratiwi, Andi Misbahul (Yayasan Jurnal Perempuan, 2019)
Political parties play an important role as a gateway to women's representation. In political party the entire battle to win seats in parliament occurs. Therefore, the policies, practices and politics in the political party determine the face of women's representation in parliament. This study focuses on policy, practice and politics in political parties in the context of encouraging women's representation in regency/city-level legislative council in Indonesia. This research explores the strategy experience and challenges faced by women legislative members in regency/city-level legislative council for the 2014-2019 period of the four parties that passed to parliament in the 2014 elections, namely PDIP, Golkar, Gerindra and one Islamic party, PPP. Data collection was carried out through in-depth interviews, focus group discussion and document review of articles of association/bylaws (AD/ART) of political parties. The results showed that 1) AD/ART of a number of political parties has adopted a 30% quota affirmative policy for party management structures and the formation of women’s party wing organizations; 2) the practices of affirmative action policies in the process of recruitment, candidacy and political campaigns have not yet fully adopted the ideology of gender mainstreaming; knowledge, programs and decisions of political parties as well as competition between legislative candidates in competing for votes are still gender biased, thus detrimental to women’s political agenda; 3) Parliamentary women experience psychological violence and intimidation in pushing the political agenda of women in parliament - rooted in patriarchal ideology, while the women’s wing have not standing for women’s agenda.